STRATEGY FOR INTERNALIZATION OF THE VALUES OF THE BOOK OF ALALA IN DEVELOPING STUDENTS MORALS IN MADRASAH DINIYAH NURUL UMMAH PUTRI ISLAMIC BOARDING SCHOOL YOGYAKARTA - Eni Fitria; Mohamad Joko Susilo (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
Learning methods in teaching carried out by teachers are sometimes still not directed. Many students violate rules and norms, such as not respecting teachers and even considering teachers to be their own friends. Therefore, the study of the previous references solved this problem. The focus of this research is what values are contained in the Alala book. What is the strategy for internalizing the values of the Alala book in fostering the morals of students. This research uses a qualitative descriptive research type. Collecting data using the method of observation, interviews, and documentation. The data analysis methods are data collection, data reduction, data presentation, and drawing conclusions. This results of this study indicate that the values contained in the Alala book are applied by students, namely, Knowledge Requirements, Virtue Knowledge, Maintaining Knowledge, Reaching Ideals, Exalting Teachers, Controlling Passions, Utilizing Time Well, Commands to Seek Knowledge. Meanwhile, the strategies for internalizing the values of the Alala book in fostering the morals of students are exemplary strategies, habituation strategies, advice strategies, story strategies and punishment strategies.